Study on impacts of engineering strategies on pedestrian behaviour and perceptions at zebra crossings - Ng, Wan Ying (2016)
A zebra crossing is a type of the pedestrian crossing with a relatively high accident risk as it is not a signalised pedestrian crossing. To cross the zebra crossings, pedestrians have to depend on themselves to look out for vehicles before and while crossing. To make matters worse, pedestrians nowadays frequently look at their mobile phones while crossing the roads, hence increasing the risk of accidents occurring at the crossings. Thus, there is a need to implement strategies at the zebra crossings to improve pedestrian safety and reduce the number of accidents. Students and the elderly are the two most vulnerable groups which are prone to accidents. The Land Transport Authority (LTA) has started painting “LOOK” markings at zebra crossings. Such “LOOK” markings have a pair of eyes and two arrows to remind pedestrians to look out for traffic before crossing the road. In order to analyse and evaluate the effectiveness of the implemented strategy, surveys were carried out at selected untreated zebra crossings as well as zebra crossings with “LOOK” sign. The survey consists of questionnaires to find out the behaviour of pedestrians at both types of zebra crossings and from there, determine the safety impact of the “LOOK” sign. Video recordings were also conducted concurrently with the survey sessions at the selected locations. Extracted data from the video footage would provide more information on the behaviour of the pedestrians. Analysis of the data was then carried out to determine the safety impacts of the “LOOK” sign. In general, results obtained stated that there are 6.9% more pedestrians looking out for vehicles before crossing at zebra crossings with “LOOK” signs than at typical zebra crossings. The questionnaire survey also supported this finding where 60% of the participants stated that the “LOOK” sign reminded them to look out for vehicles before crossing. Furthermore, zebra crossings with “LOOK” sign is also safer than typical zebra crossing as pedestrians walked 11.1% faster at zebra crossings with “LOOK” sign as compared to walking at typical crossings. This is also further supported by results obtained from the questionnaire survey where 60% of the participants ranked zebra crossings with “LOOK” as relatively safe as compared to 22% of typical zebra crossing of the same rank. In conclusion, the “LOOK” sign does improve pedestrian safety as well as remind pedestrians to look left and right before crossing. However, improvements could be made to existing zebra crossings to further improve the safety of pedestrians. One recommendation includes painting an extra “LOOK” sign at the median to remind pedestrians to look out for vehicles at the other lane while crossing the road to ensure the safety of pedestrians. 46% of the participants stated that having a “LOOK” sign at the median of the crossing will remind them to look out for vehicles and improve the safety of pedestrians at zebra crossings. Other recommendations to improve pedestrian safety would be to educate the public to increase awareness and to paint one arrow instead of two at zebra crossings to clearly indicate the direction of traffic.